2018
DOI: 10.1111/jam.14110
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediococcus pentosaceus Q6 isolated from Elymus nutans growing on the Tibetan Plateau and its application for silage preparation at low temperature

Abstract: The selection of P. pentosaceus inoculants for improving silage quality at low temperature, which provides a candidate strain to make high-quality silage in regions with frigid climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
12
2
Order By: Relevance
“…The dominant bacteria in the fresh grasses from TZ, GL, DX, and NQ were Pseudomonas, Lactobacillu, W. cibaria, and L. mesenteroides, respectively, which was also different from previous studies on fresh whole crop corn, grass, and legume forages (Ni et al, 2017;Guan et al, 2018;Liu et al, 2019;Xu et al, 2019;Yan et al, 2019). Moreover, the LAB composition in E. nutans silage is totally different that in whole crop corn silage (Xu et al, 2019). Results from the present study showed that the bacteria were mainly comprised by P. pentosaceus, Lactobacillus sp., L. mesenteroides, and L. coryniformis after 60 days of fermentation in the silage samples from TZ, while L. brevis was the dominant species in the silage samples from DX after the 14, 60, and 90 days fermentation.…”
Section: Microbial Composition Of E Nutans Before and After Ensilingcontrasting
confidence: 91%
See 3 more Smart Citations
“…The dominant bacteria in the fresh grasses from TZ, GL, DX, and NQ were Pseudomonas, Lactobacillu, W. cibaria, and L. mesenteroides, respectively, which was also different from previous studies on fresh whole crop corn, grass, and legume forages (Ni et al, 2017;Guan et al, 2018;Liu et al, 2019;Xu et al, 2019;Yan et al, 2019). Moreover, the LAB composition in E. nutans silage is totally different that in whole crop corn silage (Xu et al, 2019). Results from the present study showed that the bacteria were mainly comprised by P. pentosaceus, Lactobacillus sp., L. mesenteroides, and L. coryniformis after 60 days of fermentation in the silage samples from TZ, while L. brevis was the dominant species in the silage samples from DX after the 14, 60, and 90 days fermentation.…”
Section: Microbial Composition Of E Nutans Before and After Ensilingcontrasting
confidence: 91%
“…Therefore, the LAB succession at different fermentation stages of E. nutans was also significantly different. The dominant bacteria in the fresh grasses from TZ, GL, DX, and NQ were Pseudomonas, Lactobacillu, W. cibaria, and L. mesenteroides, respectively, which was also different from previous studies on fresh whole crop corn, grass, and legume forages (Ni et al, 2017;Guan et al, 2018;Liu et al, 2019;Xu et al, 2019;Yan et al, 2019). Moreover, the LAB composition in E. nutans silage is totally different that in whole crop corn silage (Xu et al, 2019).…”
Section: Microbial Composition Of E Nutans Before and After Ensilingcontrasting
confidence: 75%
See 2 more Smart Citations
“…As a major advance in the application of animal husbandry, P. pentosaceus DSM 16,244 was certified as safe additive for all animal species by the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) [67]. With regard to crops, Elymus nutansderived P. pentosaceus Q6 was beneficial for the storage quality of Elymus nutans silages at low temperature [16]. Thus, P. pentosaceus Q6 might be a cold-resistant candidate for high-quality silage storage.…”
Section: Evidence Of P Pentosaceus Use In Food Engineering Agricultmentioning
confidence: 99%